Peculiarities of development and efficiency of transport infrastructure usage in the countries of Economic Cooperation Organization (ECO) - Bilovska, Olga; Khanova, Elena (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2018)
The article considers peculiarities of development and efficiency of transportusage infrastructure in the countries of Economic Cooperation Organization (ECO). The research emphasizes the considerable territorial inequality of transport infrastructure development in the considered countries. Estimation of the level of transport infrastructure provision with the help of Engelcoefficient has proved that the ECO countries which are best provided with railroad infrastructure are Azerbaijan, Kazakhstan and Turkmenistan, and the least provided countries are Kyrgyzstan, Tajikistan and Pakistan.  The author identidies the basic goal and task of the transport logistics. Analysis of efficiency of transport infrastructure functioning in the countries as well the level of their integration in the world transport system has been carried out via index of transport logistics efficiency within the period of 2007 – 2016